2018
DOI: 10.1029/2017jf004542
|View full text |Cite
|
Sign up to set email alerts
|

Decadal‐Scale Riverbed Deformation and Sand Budget of the Last 500 km of the Mississippi River: Insights Into Natural and River Engineering Effects on a Large Alluvial River

Abstract: Alluvial rivers are shaped by interactions of flow and sediment transport. Their lower reaches to the world's oceans are highly dynamic, often presenting engineering and management challenges. Here we analyzed over 6,000 single-beam cross-sectional measurements surveyed in 1992, 2004, and 2013 in the last 500-km reach of the highly engineered Mississippi River, also known as the lowermost Mississippi River or LmMR, starting from the river's Gulf outlet to its avulsion into the Atchafalaya River. We applied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
69
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 54 publications
14
69
2
Order By: Relevance
“…They concluded that, since the LMR generally received less flow than it did beforehand due to ORCS regulation, there were lower water velocities, which could further benefit in sediment deposition along the reach. Similar observations with sediment deposition in the LMR were also observed by Biedenharn et al [50], as well as Wang and Xu [14]. Biedenharn et al [50] analyzed the stage and discharge data from gauging stations from 1880-1992 and summarized that the river in the post-cutoff period (1943-1992) had a much greater stream power than in the pre-cutoff (1880s-1930s).…”
Section: Study Sitesupporting
confidence: 74%
See 3 more Smart Citations
“…They concluded that, since the LMR generally received less flow than it did beforehand due to ORCS regulation, there were lower water velocities, which could further benefit in sediment deposition along the reach. Similar observations with sediment deposition in the LMR were also observed by Biedenharn et al [50], as well as Wang and Xu [14]. Biedenharn et al [50] analyzed the stage and discharge data from gauging stations from 1880-1992 and summarized that the river in the post-cutoff period (1943-1992) had a much greater stream power than in the pre-cutoff (1880s-1930s).…”
Section: Study Sitesupporting
confidence: 74%
“…Due to preventing the main channel of Mississippi River from suddenly changing its course (avulsion) into the Atchafalaya River [3], the first phase of the Old River Control Structure (ORCS) was completed in 1963 by the United States Army Corps of Engineers (USACE). After the completion of these structures, different studies discussed whether the ORCS blocked sediments and resulted in sediment deficiency, or stabilized the channel gradient and caused riverbed aggradation [4][5][6][7][8][9][10][11][12][13][14][15][16]. In a recent modeling study, Wang and Xu [17] found that, proportionally, more riverbed materials were carried downstream in the Mississippi mainstem than to the outflow channel.…”
Section: Study Aimsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Wang and Xu pointed out that the diverted sediment may be lower than the transport capacity of the diversion Outflow Channel, it is largely unknown how much sediment, especially the bed material load (i.e., sediment comprising the bed that travels either as bedload or suspended load), is actually diverted via the Outflow Channel to the Atchafalaya River. The information is critical because studies have found considerable channel aggradation immediately downstream of the ORCS on the Mississippi River mainstem (Mossa, 2013; Wang & Xu, 2018a), which could cause backwater during floods threatening the diversion structure.…”
Section: Introductionmentioning
confidence: 99%